PENGARUH PESAN DI MEDIA SOSIAL INSTAGRAM TERHADAP SIKAP PENGGUNAAN PLASTIK SEKALI PAKAI (Survei Pada Followers Media Sosial Instagram @demibumi.id) - Camila Muslih (2023)
This study aims to determine whether there is a change in people's attitude towards messages on social media Instagram @demibumi.id which provide information regarding the use of single-use plastics. The theory used in this research is Information Integration Theory. This research was conducted with a quantitative approach. The method used is survey method. The population of this research is followers from the Instagram account @demibumi.id with a sample of 100 respondents. The results of the correlation test stated that messages on social media Instagram @demibumi.id had a strong relationship with attitudes towards using single-use plastics. The results of the linear regression test and the results of the coefficient of determination test showed that there was a positive effect of 42% from messages on the social media Instagram @demibumi.id on the attitudes of Instagram followers @demibumi.id regarding the use of single-use plastics. Thus, it can be concluded that there is an influence of messages on social media Instagram @demibumi.id on attitudes towards the use of single-use plastics.